The war for independence : the story of the American Revolution - Marrin, Albert (New York : Atheneum, 1988)
A detailed account of the Revolutionary War beginning with its origins in the French and Indian War.
Includes index.
Bibliography: p. 267-270.
Keywords: United States -- History -- Revolution, 1775-1783 -- Juvenile literature; United States -- History -- Revolution, 1775-1783.